The Impact of SARD-Based Cooperative Learning with the Patik Bali Application on Motivation and Learning Outcomes in Balinese Script Instruction Abstract - Muliana, I Kadek Eka; Martha, Nengah; Dewantara, I Putu Mas (LP. Ma'arif Janggan Magetan, 2025)
Balinese script learning in schools still faces obstacles of low motivation and student learning outcomes due to the use of conventional models that do not actively involve students. The study aims to determine the effectiveness of the Student Teams Achievement Division (STAD) type cooperative learning model based on the Patik Bali application on students' motivation and learning outcomes in writing Balinese script. This study uses a quasi-experimental design method with the subjects of class X students of SMA Negeri 10 Denpasar which is divided into experimental classes and control classes. The instruments used included learning outcome tests and learning motivation questionnaires. Data analysis was carried out using the MANOVA test to see the effect of the learning model on two variables that rotate simultaneously. The results of the study show that the Patik Bali application-based STAD model has a positive and significant influence on student motivation and learning outcomes. The average learning motivation of the experimental class was 72.78 and the learning outcome was 81.86 higher than the control class which obtained an average motivation of 61.25 and learning outcomes of 75.25. These findings show that the integration of technology through the Patik Bali application in the cooperative learning model can increase student participation and understanding in Balinese script learning. This research offers a new contribution by integrating the culture-based Patik Bali application into the STAD cooperative learning model specifically designed for Balinese literacy learning and combining regional language preservation with digital pedagogy to improve student motivation and learning outcomes.